(untitled) (Swiss Medical Weekly, 2013)
Heart transplantation is only available for a limited number of patients with end-stage heart failure. Since the arrival of newer ventricular assist devices, mechanical circulatory support constitutes an alternative therapy for patients with advanced heart failure. The first-generation of pulsatile-flow devices were used only for bridging the sickest patients to transplantation. Frequent adverse events, limited durability and the patients’ discomfort made them unsuitable for lifetime support. The second-generation continuous-flow devices were smaller, quieter and more durable. Survival rates of patients improved significantly. This led to a marked growth of device implantations, largely caused by an increase of lifetime support. Survival of destination therapy patients is somewhat inferior to the survival of bridge-to-transplant patients, in part due to their co-morbid conditions which limit life expectancy. A subgroup of patients on destination therapy with advanced, but stable heart failure and a low-risk profile reach short-term survival rates equal or superior to the survival after heart transplantation. These patients may be offered the choice of destination therapy versus heart transplantation. However it remains unclear if long-term survival, quality of life and functional status on lifetime support can compete with the excellent results after transplantation. A trend to implanting devices at earlier stages of heart failure has begun. In a current trial, patients with advanced, but stable heart failure are randomised to destination therapy versus optimal medical therapy. The results of this trial will be expected to more precisely determine the place of mechanical circulatory support in the treatment of advanced heart failure.